Probiotic compositions and methods of promoting child growth and social function using same - KONG XUEJUN (2023)
Disclosed herein are methods and compositions useful for treating a subject suffering from Prallard-Willard Syndrome (PWS). The methods comprise administering to a subject in need thereof a composition comprising probiotics (e.g., Lactobacillus reuteri (L.reuteri) and Bifidobacterium animalis subsp. Lactis (B.lactis). 本文公开了可用于治疗患有普拉德-威利综合征(PWS)的对象的方法和组合物。所述方法包括向有需要的对象施用包含益生菌(例如罗伊氏乳杆菌(L.reuteri)和动物双歧杆菌乳亚种(B.lactis))的组合物。